Impulsivity, Unplanned Pregnancies, and Contraception Among Women with Bipolar Disorder - Zengin Eroglu M (Dove Medical Press, 2020)
Meliha Zengin Eroglu,1 Melek Gözde Lus2 1Haydarpasa Numune Training and Research Hospital, Department of Psychiatry, Uskudar-Istanbul 34668, Turkey; 2Department of Child and Adolescent Psychiatry, Haydarpasa Numune Training and Research Hospital, Uskudar-Istanbul 34668, TurkeyCorrespondence: Meliha Zengin ErogluHaydarpasa Numune Training and Research Hospital, Department of Psychiatry, Selimiye Mah, Tıbbiye Cad, No: 23, Uskudar-Istanbul 34668, TurkeyTel +90 216 542 32 32Fax +90 2163360565Email melihazengin@gmail.comBackground: Impulsivity is one of the principal symptoms of bipolar and related disorders (BD). Unsafe sex and unplanned pregnancies are serious problems in clinical practice. The aim of this study was to investigate impulsivity levels, contraception methods, and levels of planned pregnancies among women with bipolar and related disorders (WBD).Methods: Fifty-eight euthymic women with BD (bipolar disorder type I, II, or other) were matched by education levels with a control group of 59 healthy women. Data about their demographic, clinical—Barratt Impulsiveness Scale (BIS-11), Hamilton Depression Rating Scale, and Young Mania Rating Scale scores—and reproductive health features were obtained and compared between the groups.Results: No difference was found regarding BIS-11 (total, nonplanning, motor, and attentional subscales) scores between the WBD and control groups. The overall rate of contraception use was higher in WBD (96.6%), but they generally preferred “traditional” methods (i.e., withdrawal and calendar). The total rate of unplanned pregnancies in WBD was 49.52%. Rate of unplanned pregnancies in WBD was significantly different from women without bipolar disorder (49.52% vs 15.04%).Discussion: Levels of impulsivity in euthymic WBD under treatment were similar to those of healthy women in the control sample. WBD paid attention to contraception although they usually used traditional methods. The findings indicate that most WBD use contraception, yet the contraception is potentially ineffective especially if WBD have more unplanned pregnancies. The provision of an effective contraception method in WBD is suggested for all clinicians, in order to prevent sexually transmitted diseases and unplanned pregnancies, and thus protect the health of both mother and fetus.Keywords: impulsivity, contraception, pregnancy, reproductive function, bipolar disorder, euthymia